ACTR-34. SINGLE AGENT ONC201 IN PREVIOUSLY-TREATED, PROGRESSIVE ADULT H3 K27M-MUTANT GLIOMA. (11th November 2019) - Arrillaga-Romany, Isabel; Kurz, Sylvia; Sumrall, Ashley; Butowski, Nicholas; Harrison, Rebecca; DeGroot, John; Chi, Andrew; Sulman, Erik; Shonka, Nicole; Umemura, Yoshie; Odia, Yazmin; Mehta, Minesh; et al.
Abstract: H3 K27M-mutant gliomas often manifest as midline gliomas, have a dismal prognosis, and have no established or effective treatments at recurrence. ONC201 is the first clinical bitopic DRD2 antagonist/ClpP agonist and is under evaluation in Phase II trials for gliomas and other cancers. We previously reported in vitro studies suggesting dysregulated dopamine receptor expression and enhanced ONC201 sensitivity among H3 K27M-mutant gliomas. Following these observations, adults with midline H3 K27M-mutant glioma patients were enrolled to a dedicated Phase II clinical trial (NCT03295396), a multi-arm Phase II trial (NCT0252569), and expanded access protocols under the Sponsor's IND. An integrated radiographic analysis with an objective response rate primary endpoint in patients who received ONC201 monotherapy with confirmed H3 K27M-mutant glioma (not primarily in the pons or spinal cord and without leptomeningeal spread) that was progressive and measurable disease by RANO criteria, >90 days from completion of prior radiation, and had KPS >60. As of December 15, 2018, 15 patients have received single agent ONC201 who meet these criteria (n=9 NCT03295396; n=5 NCT0252569; n=1 expanded access). ONC201 was orally administered at 625 mg weekly, except for one patient dosed once every 3 weeks. As midline gliomas can exhibit a mixture of contrast-enhancing and non-contrast-enhancing disease, objective response was assessed by blinded independent central review using RANO-HGG and RANO-LGG criteria for each patient. Best response to date by RANO-HGG criteria is at least 27%: 1 CR, 3 PR, 7 SD, and 4 PD; by RANO-LGG is at least 36%: 1 CR, 1 PR, 3 minor response (MR), 4 SD, 5 PD, 1 unevaluable. By RANO-HGG, median onset of response is 2.6 months (range 1.3–3.4); median duration of response has not been reached with a median follow-up of 7.7 months (range 1.8–29.8). Updated radiographic response, pharmacodynamics, safety, and other clinical outcomes will be reported.